PENERAPAN MODEL PEMBELAJARAN ICARE (INTRODUCTION CONNECTION APPLICATION REFLECTION EXTENTION) UNTUK MENINGKATKAN HASIL BELAJAR TEKNOLOGI INFORMASI DAN KOMUNKASI (TIK) (Studi Kasus: Siswa Kelas VIII.3 SMP Laboratorium Undiksha Singaraja Tahun Ajaran 2013-2014) - Putu Yuli Krisnawati; Nyoman Sugihartini; Made Windu Antara Kesiman; Dessy Seri Wahyuni (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
This study aimed at improving students' learning outcomes on the subject of Technology of Information and Communication by implementing ICARE (Introduction Connection Application Reflection Extention) instructional model and finding out the students' responses toward the implementation of ICARE instructional model. This research was conducted at SMP Laboratorium Undiksha Singaraja which involved the students of class VIII.3 (29 students) in the academic year 2013/2014. This research was designed in the form of Class Action Research which consisted of 2 cycles. The data which were gathered in this research were the students' learning outcomes and responses toward the implementation of ICARE instructional model on the subject of Technology of Information and Communication. The data of the students' learning outcomes were gathered by means of cognitive test as well as affective and psikomotor observation sheet, while the data of the students' responses were gathered by closed questionnaire. The result of this study showed that (1) there was an improvement of the students' learning outcomes. This can be seen from the classical mastery of the students obtained in the fist cycle was 17.24%, and in the second cycle was 100.00%. The learning outcomes improved by 82.76%. (2) The students' responses on the average toward the implementation of ICARE instructional model could be classified as positive that was equal to 47.07. The researcher concluded that the implementation of ICARE instructional model on on the subject of Technology of Information and Communication can improve the students' learning outcomes and can obtain postive responses from the students.